2015
DOI: 10.5114/pm.2015.56540
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles as a potential biomarker of neoplastic diseases and their role in development and progression of neoplasm

Abstract: Neoplastic diseases together with cardiovascular diseases are the most frequent causes of death in the Polish population. Cancers of reproductive organs with breast cancer are responsible for the highest morbidity and mortality in women suffering from neoplasm diseases. Asymptomatic dynamics of the development of a neoplasm and no deviations from the normal level of laboratory results contribute to the fact that malignant diseases are diagnosed too late. The aim of modern medicine is to diagnose cancer at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…: 25 Presence of phosphatidylserine on the cell surface (externalization) along with Annexin, FasL/FasR, TNFα/ TNFR1Apo2L/DR5 21 Contents MHC, miRNA, Non-coding RNA 27 Cytoplasmic protein, Membrane proteins, Receptor proteins, miRNA, mRNA 28 Various cell organelles, DNA, Nuclear fractions. 29 Biomarkers TSPAN29, TSPAN30, CD81, CD82, CD9 TSG101, CD63 30 Integrins, selectins, metalloproteinase 31 Annexin V positive and phospatidylserine (PS) 32 glycoprotein) peptide of rabies virus fused to LAMP-2B was effectively delivered to acetylcholine receptors and hence delivered drugs to specific areas of the brain. This has been used in targeted therapy of Alzheimer's disease and it also helps in neurogenesis.…”
Section: Compositionmentioning
confidence: 99%
“…: 25 Presence of phosphatidylserine on the cell surface (externalization) along with Annexin, FasL/FasR, TNFα/ TNFR1Apo2L/DR5 21 Contents MHC, miRNA, Non-coding RNA 27 Cytoplasmic protein, Membrane proteins, Receptor proteins, miRNA, mRNA 28 Various cell organelles, DNA, Nuclear fractions. 29 Biomarkers TSPAN29, TSPAN30, CD81, CD82, CD9 TSG101, CD63 30 Integrins, selectins, metalloproteinase 31 Annexin V positive and phospatidylserine (PS) 32 glycoprotein) peptide of rabies virus fused to LAMP-2B was effectively delivered to acetylcholine receptors and hence delivered drugs to specific areas of the brain. This has been used in targeted therapy of Alzheimer's disease and it also helps in neurogenesis.…”
Section: Compositionmentioning
confidence: 99%
“…The latest study has proved that there is a difference in the expression of exosomes in the blood of patients with OC and normal people, and the expression in the body fluid of patients with OC is related to the stage of the tumor [99]. A total of 1017 co-expressed proteins were screened from the exosomes secreted by two kinds of OC cells, among which tubulin beta 3 class III (TUBB3), epithelial cell adhesion molecule (EpCAM), claudin 3 (CLDN3), proliferating cell nuclear antigen (PCNA), epidermal growth factor receptor (EGFR), and fatty acid synthase (FASN) were highly enriched in tumor-related signal pathways.…”
Section: Ovarian and Cervical Cancermentioning
confidence: 99%
“…Recent studies have revealed that exosomes can transport enzymes from EOC cells. Furthermore, an increased level of exosomes in the peritoneal fluid has been found to be correlated with tumor progression [ 18 , 19 ], indicating that the level of exosomes in the blood is correlated with the stage of OC. Thus, exosomes themselves and their contents have potential as tumor-specific markers.…”
Section: Exosomes As Biomarkers Of Ocmentioning
confidence: 99%